The anatomy of Continental Flood Basalt Provinces : geological constraints on the processes and products of flood volcanism. - Jerram, D. A.; Widdowson, M. (Lithos, 2005)
The internal architecture of the immense volumes of eruptive products in Continental Flood Basalt Provinces (CFBPs) provides vital clues, through the constraint of a chrono-stratigraphic framework, to the origins of major intraplate melting events. This work presents close examination of the internal facies architecture and structure, duration of volcanism, epeirogenetic uplift associated with CFBPs, and the potential environmental impacts of three intensely studied CFBPs (the Parana-Etendeka, Deccan Traps and North Atlantic Igneous Province). Such a combination of key volcanological, stratigraphic and chronologic observations can reveal how a CFBP is constructed spatially and temporally to provide crucial geological constraints regarding their development. Using this approach, a typical model can be generated, on the basis of the three selected CFBPs, that describes three main phases of flood basalt volcanism. These phases are recognized in Phanerozoic CFBPs globally. At the inception of CFBP volcanism, relatively low-volume transitional-alkaline eruptions are forcibly erupted into exposed cratonic basement lithologies, sediments, and in some cases, water. Distribution of initial volcanism is strongly controlled by the arrangement of pre-existing topography, the presence of water bodies and local sedimentary systems, but is primarily controlled by existing lithospheric and crustal weaknesses and concurrent regional stress patterns. The main phase of volcanism is typically characterised by a culmination of repeated episodes of large volume tholeiitic flows that predominantly generate large tabular flows and flow fields from a number of spatially restricted eruption sites and fissures. These tabular flows build a thick lava flow stratigraphy in a relatively short period of time (c. 1–5 Ma). With the overall duration of flood volcanism lasting 5–10 Ma (the main phase accounting for less than half the overall eruptive time in each specific case). This main phase or ‘acme’ of volcanism accounts for much of the CFBP eruptive volume, indicating that eruption rates are extremely variable over the whole duration of the CFBP. During the waning phase of flood volcanism, the volume of eruptions rapidly decrease and more widely distributed localised centres of eruption begin to develop. These late-stage eruptions are commonly associated with increasing silica content and highly explosive eruptive products. Posteruptive modification is characterised by continued episodes of regional uplift, associated erosion, and often the persistence of a lower-volume mantle melting anomaly in the offshore parts of those CFBPs at volcanic rifted margins.